Axial length measurement techniques in pediatric eyes with cataract - Wilson, M. Edward (Elsevier, 2011)
Globe axial length (AL) in children is commonly measured using either contact or immersion technique. Office measurement of AL can be difficult in young children and infants and must often be done under anesthesia in an eye that is unable to cooperate with precise fixation and centration. Contact A-scan measurements yield shorter AL, on average, than immersion A-scan measurements in pediatric eyes. This difference is mainly the result of the anterior chamber depth rather than the lens thickness value. During intraocular lens power calculation, if globe axial length is measured by the contact technique, it will result in the use of an average 1-D stronger IOL power than is actually required. This can lead to induced myopia in the postoperative refraction. In our studied patients, there was a significant difference in prediction error between contact A-scan biometry and immersion A-scan biometry. The immersion A-scan technique is recommended for pediatric IOL power calculation. We also provide a review of biometry in pediatric eyes. The overall mean AL of pediatric cataractous eyes is significantly different than the mean AL of non cataractous eyes. More importantly, the standard deviation is higher in eyes with cataract than in those without. Three phases of eye growth in children have been documented: A rapid, postnatal phase from birth to 6 months of age, followed by a slower, infantile phase from 6 to 18 months of age, and finally a slow, juvenile phase from 18 months forward. In our study, girls had shorter ALs than boys and African-American subjects had longer ALs than Caucasians. Eyes with unilateral cataract had shorter ALs than eyes with bilateral cataract during the earlier years, but had longer ALs during later childhood.